Insulating material based on shredded used tires and inexpensive polymers for different roofs - Zakaria, Fatma; A. Radwan, M.; A.Sadek, M.; A.Elazab, Hany (International Journal of Engineering and Technology, 2018)
Thermal insulation is the ability of the material to prevent or reduce the heat transfer through the insulating material or between thermally contacted objectives. The increasing of the greenhouse effect leads to a continuous rising of the temperature especially in the summer, thus, there is a continuous research that aims to find more effective and environmental friendly insulation materials. Nowadays, a great number of proportions from polyurethane foam are produced every year in order to be used as an insulating material. Polyurethane foam shows an effective heat insulation results, but the price of the polyurethane is getting more expensive each day in Egypt due to the continuous rising of the hard currency as it is imported from abroad. This paper aims to prepare, design and develop effective heat insulation composite based on shredded used automobile tires. This was done by preparation different ratio composite from shredded used automobile tires and polyester along with polyurethane and shredded used automobile tires. These heat insulation tiles were characterized by the following testing, thermal insulation test, compression test, density measurement, abrasion test to measure the effect of adding the shredded used automobile tires to these polymers. It was found that, the composite of 66.7 wt % polyurethane foam and 33.3 wt % shredded automobile tires was the best choice to be used as it provides efficient thermal insulation of K value of 0.1663 W/m.â„ƒ. It also has a low density of 0.0313 kg/l. Furthermore, the addition of shredded used automobile tires reduces the cost by 33%. Furthermore, the compression strength of the polyurethane foam was increased by adding the shredded used automobile tires. Hence, using cheap materials such as shredded used tires, which considered as undesirable waste material, results in both producing a cheap national heat insulating roof tile with good mechanical, waterproofing and thermal insulating characteristics along with solving a serious environmental problem that occurs to get rid of the shredded waste automobile tires, as in some cases the tires are being burned resulting in air pollution and causing various diseases, which finally leading to more waste treatment management strategies. Finally, this heat insulation composite directly results in lowering the energy consumption required to cooling and heating systems inside the buildings.Â